LITERASI KUANTITATIF SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI GAYA BELAJAR - Sely Purwanti Ningsih; I Ketut Budayasa; Siti Khabibah (IKIP Siliwangi, 2023)
This research method is descriptive qualitative which aims to describe the quantitative literacy of junior high school students in solving mathematical problems in terms of visual, auditory, and kinesthetic learning styles. Research subjects were selected by giving a learning style questionnaire and grade VIII math scores in odd semesters. The test given was a problem-solving test in the form of a description of 3 questions and interviews containing questions to explore student answers in solving problems, and drawing conclusions. The results showed that (1) students with a visual learning style do: representation by making and explaining frequency distribution tables; student analysis shows that they believe that the information provided is useful for solving problems; assumptions and communications to explain the processes used in solving problems. (2) students with auditory learning style do: interpretation by understanding diagrams to understand problems and plan problem solving; calculation in planning, implementing, and reassessing by explaining how to calculate; analysis that is confident about the results of the solution being worked on. (3) students with a kinesthetic learning style interpret by reading graphs and questions on questions to understand and plan problem solving.